Land grab - Barton, Miles; BBC Learning (Australia: BBC Learning, 2005)
This series visits the crucial moments in life's journey to dominate the earth.'Land grab' follows life as it changes from a fish to a human
Photography, Simon wagen ; executive producer, Michael Gunton ; series producer, Miles Barton
Keywords: Evolution; Evolution (Biology).